Pengaruh Work-Life Balance dan Beban Kerja Terhadap Turnover Intention Melalui Kepuasan Kerja Pada Karyawan PT Misaja Mitra Pati - Karina Fitria Utami; Qristin Violinda; Farah Chalida Hanoum (PT. Alahyan Publisher Sukabumi, 2026)
Turnover intention is one of the major challenges faced by organizations as it increases recruitment and training costs while reducing employee productivity. This study aims to analyze the effects of work-life balance and workload on turnover intention, with job satisfaction as a mediating variable among employees of PT Misaja Mitra Pati. This research employed a quantitative approach using a survey method. Data were collected through a Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. The results indicate that workload has a positive and significant effect on both job satisfaction and turnover intention, while work-life balance has a positive and significant effect on job satisfaction. Furthermore, job satisfaction has no significant effect on turnover intention and does not mediate the relationship between workload, work-life balance, and turnover intention. These findings suggest that effective workload management and the improvement of work-life balance are essential strategies to enhance employee retention and reduce turnover intention.